(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The evaluation of public policies is associated, every time in less extent, in an ex-post moment inside of a cycle plan, program, policy or project, however it is necessary that the evaluation will be viewed from a comprehensive stand point of view. The objectives of this paper are on one side to stimulate for further debates through the academy over the evaluation of public policies and the challenges that deal with a scene of national and local governance, on the other hand to provide knowledge about the evaluation of public policies, which determine the impact thereof and together help develop a culture of evaluation. To do this, essentially what is done in this paper is to start by establishing individually concepts both public policies and evaluation, later to approach the evaluation of public policies as a whole, expounding conceptualizations of it, historical evolution of the development of evaluation, its importance, necessity and function. As a result, it is confirmed the practical utility of the evaluation of public policies as a tool to improve the public interventions in a win-win relationship by the government and the governed. DOI: http://dx.doi.org/10.5377/reice.v2i4.1724 REICE Vol. 2, No. 4, julio-diciembre 2014: 34-48